THE RELATIONSHIP BETWEEN SYNCHRONOUS LEARNING DEXTERITY AND ASYNCHRONOUS LEARNING DEXTERITY WITH STUDENT LEARNING PERFORMANCES IN HIGHER EDUCATION - Kardipah, Seipah; Winanti, Yunea Kusuma (Akademika : Jurnal Teknologi Pendidikan, 2025)
This study analyzes the relationship between students' synchronous and asynchronous learning dexterity and their learning performance in an online learning environment in higher education. Using a quantitative correlational design, data were collected from 33 graduate students through asynchronous and synchronous learning agility questionnaires and final course grades. Data were analyzed using Spearman's rho correlation to determine the strength and direction of the relationships between variables. The results showed a strong, positive, and significant correlation between student learning outcomes and synchronous learning dexterity (r = .867, p < .01) and asynchronous learning dexterity (r = .725, p < .01). These findings suggest that students who are agile in both real-time and self-paced learning activities achieve higher learning outcomes. This investigation demonstrates the value of instructional design in integrating synchronous learning approaches with asynchronous learning flexibility to enhance student engagement and learning outcomes. Overall, these results provide empirical support for designing adaptive learning models that balance both modes (synchronous and asynchronous) to optimize student performance and student experience in higher education.